Kecerdasan Emosional, Adaptabilitas Karier, dan Kepuasan Karier pada Karyawan Garis Depan - Lingga Sundagumilar Abqari; Asep Mulyana; Yunizar Yunizar; Muhammad Fajar Wahyudi Rahman (Jurnal Ilmu Manajemen, 2023)
This study aims to advance research on career construction theory and cognitive-affective processing systems theory by examining the theorized but untested relationship between emotional intelligence, career adaptability and career satisfaction. More precisely, exploring the relationship between emotional intelligence, career adaptability, and career satisfaction. This research was conducted on frontline employees who interact directly with customers. The Structural Equation Model (SEM) approach, with the help of SmartPLS, was carried out in this quantitative study. The results found in this study are emotional intelligence which directly influences career adaptability and career satisfaction. Meanwhile, the effect of career adaptability on career satisfaction was not found. In addition, this study also found that the career adaptability variable had no effect in mediating the relationship between emotional intelligence and career satisfaction. The results of this study can motivate frontline employees to have the good emotional intelligence to adapt their careers for a promising future and achieve career satisfaction.